Cellular Senescence: A Bridge Between Diabetes and Microangiopathy - Jiahui Liu; Buyu Guo; Qianqian Liu; Guomao Zhu; Yaqi Wang; Na Wang; Yichen Yang; Songbo Fu (Biomolecules)
Cellular senescence is a state of permanent cell cycle arrest and plays an important role in many vascular lesions. This study found that the cells of diabetic patients have more characteristics of senescence, which may cause microvascular complications. Cell senescence, as one of the common fates of cells, links microangiopathy and diabetes. Cell senescence in a high-glucose environment can partially elucidate the mechanism of diabetic microangiopathy, and various types of cellular senescence induced by it can promote the progression of diabetic microangiopathy. Still, the molecular mechanism of microangiopathy-related cellular senescence has not yet been clearly studied. Building on recent research evidence, we herein summarize the fundamental mechanisms underlying the development of cellular senescence in various microangiopathies associated with diabetes. We gradually explain how cellular senescence serves as a key driver of diabetic microangiopathy. At the same time, the treatment of basic senescence mechanisms such as cellular senescence may have a great impact on the pathogenesis of the disease, may be more effective in preventing the development of diabetic microangiopathy, and may provide new ideas for the clinical treatment and prognosis of diabetic microangiopathy.